MAKNA KEHIDUPAN MANUSIA MENURUT ALBERT CAMUS - Allien, Astri Adriani (Faculty of Humanities, Diponegoro University, 2012)
Albert Camus is an important figure in the history of French literature with his main themes, absurdity and suicide. Using the method of intertextuality, this paper analyses Camus’ thoughts on the absurd meaning of life portrayed through the character Mersault in his work L’Etranger. It is then found that this work carries the same philosophical ideas of absurdity as found in his famous essay Le Mythe de Sysiphe, and make those ideas more easily understood. The difference between those two works is just of genre. Keywords: Albert Camus, L’Etranger, intertextuality, absurdity